How to Enhance the Green Innovation of Sports Goods? Micro- and Macro-Level Evidence From China’s Manufacturing Enterprises - Huang, Chengyin; Chen, Ying (Frontiers in Environmental Science, 2022)
This study aims to explore the driving factors of green innovation, and uses the micro- and macro-data from China’s sports goods manufacturing industries. In particularly, sports goods manufacturing enterprises are identified by adopting the textual analysis of information disclosure, and the competitive environment faced by each enterprise is built by their closest rivals. Empirically, this study finds that competition and policy can promote green innovation in sports goods manufacturing industries. Moreover, industrial policy can moderate the role of product market competition in promoting green innovation. It is worth noting that the association between product market competition and green innovation changes as financial constraints increase, and this may be credited to the influence of industrial policy. After implementing the strict environmental policy, product market competition and industrial policy can both promote green innovation. Furthermore, sports goods manufacturing enterprises in high-polluting industries can get more motivations from industrial policies to support green innovation. In addition, we also find that there is a significant inverted-U shape relationship between industrial policy and green innovation in sports goods manufacturing industries. As financial constraints increase, the non-linear relationship between product market competition and green innovation converts from a U shape relationship to an inverted-U shape relationship. Our findings can pro-vide a better understanding of the investment of sports goods manufacturing enterprises in green innovation.